2022
DOI: 10.1111/jeb.14126
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection drives the coevolution of male and female reproductive traits in Peromyscus mice

Abstract: When females mate with multiple partners within a single reproductive cycle, sperm from rival males may compete for fertilization of a limited number of ova, and females may bias the fertilization of their ova by particular sperm. Over evolutionary timescales, these two forms of selection shape both male and female reproductive physiology when females mate multiply, yet in monogamous systems, post‐copulatory sexual selection is weak or absent. Here, we examine how divergent mating strategies within a genus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…In monogamous P. californicus , male-male competition is reduced and postcopulatory sexual selection should be weak in comparison with polygynandrous P. maniculatus and P. boylii . A recent study showed that traits under postcopulatory sexual selection, such as sperm production efficiency and sperm swimming speed, are increased and show a stronger correlation with female defensiveness traits such as oviduct length in more polygynandrous Peromyscus (Weber and Fisher 2023). This suggests that the extent of both male-male competition and male-female sexual conflict varies with mating behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In monogamous P. californicus , male-male competition is reduced and postcopulatory sexual selection should be weak in comparison with polygynandrous P. maniculatus and P. boylii . A recent study showed that traits under postcopulatory sexual selection, such as sperm production efficiency and sperm swimming speed, are increased and show a stronger correlation with female defensiveness traits such as oviduct length in more polygynandrous Peromyscus (Weber and Fisher 2023). This suggests that the extent of both male-male competition and male-female sexual conflict varies with mating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Adgrd1 is an MS-DEG with reduced expression in the P. californicus seminal vesicle and epididymis. Exploring female reproductive tract gene expression would address whether any 'male fertility' genes are expressed in the female reproductive tract or vice versa and would contribute to our understanding of female defense traits such as egg extracellular matrix and uterine fluid composition (Hook et al, 2022;Weber and Fisher 2023).…”
Section: Integrating Gene Sequence and Expression Evolutionmentioning
confidence: 99%
See 1 more Smart Citation